2019
DOI: 10.1002/ca.23512
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Reconstruction of the Genial Spinal Canal

Abstract: The aim of this anatomical study was to investigate the genial spinal canal histologically and to reconstruct it three‐dimensionally to improve understanding of its anatomy and to reveal any differences between dentate and edentulous specimens. Two tissue blocks from the mandible between the left and right second incisors, one dentate and one edentulous, were fixed in 4.5% formaldehyde, decalcified and embedded in paraffin. Serial histological sections were prepared, stained with Azan and examined microscopica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…According to a cadaver study, it is most likely that the nerve canal running in the center of the anterior mandible, the so called "genial spinal canal", is hit when a central single implant is inserted [82]. It is possible, however, that the bundle of nerve vessels running in this canal is degeneratively altered to such an extent in edentulous patients [83] that its damage has no clinically relevant consequences. In a clinical investigation on 50 edentulous patients receiving a single implant in the anterior mandible, neurosensory complications in the mandible were analyzed [84].…”
Section: Discussionmentioning
confidence: 99%
“…According to a cadaver study, it is most likely that the nerve canal running in the center of the anterior mandible, the so called "genial spinal canal", is hit when a central single implant is inserted [82]. It is possible, however, that the bundle of nerve vessels running in this canal is degeneratively altered to such an extent in edentulous patients [83] that its damage has no clinically relevant consequences. In a clinical investigation on 50 edentulous patients receiving a single implant in the anterior mandible, neurosensory complications in the mandible were analyzed [84].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent anatomical study curried on dentate and edentulous cadaveric mandibles investigated the genial spinal canal histologically concluded that the genial spinal canal in the dentate specimen contained a neurovascular bundle, which branched into a nerve innervating the incisor and a neurovascular bundle, whereas that in the edentulous specimen contained some nerves for vestibular gingival innervation and a vascular bundle [ 62 ]. The results propose differences in the genial spinal canal between dentate and edentulous mandibles and may explain the low incidence of both vascular or neurosensory complications in the current study.…”
Section: Discussionmentioning
confidence: 99%